Avoiding Food Wastage: The Net Impact of Maisto Bankas Activities. A Carbon Footprint Approach - Meloni Giuditta; Rocchi Lucia (Environmental and Climate Technologies, 2022)
Food wastage is a complex global issue. Its solution requires a multi-pronged effort and the use of diversified strategies. Since the impacts are on an environmental, social and economic level, solutions can take shape in one of these areas, knowing that there are often trade-offs between one and the other. This paper aims to evaluate the net environmental effects in terms of Carbon footprint of the activities of the Lithuanian Food Bank (Maisto Bankas). Food banks are charities that work to reduce the negative social effects associated with food waste and food insecurity. They work on the food recovery, avoiding the transformation of food surplus in food waste. The present paper assessed the positive impact generated by the Lithuanian Food Bank thanks to its activities as the non-impact of recovered food and the non-disposal of food in landfills. At the same time, also the negative impact in term of emission due to the management of all its activities has been estimated. The net impact has been derived by the comparison of the two flows. The results of the study proved that, behind the social benefit, the Food Banks, as Maisto Bankas, produce also a net positive environmental impact.